2018
DOI: 10.1080/02713683.2018.1490773
|View full text |Cite
|
Sign up to set email alerts
|

Primary Descemet’s Membrane Endothelial Keratoplasty for Fuchs Endothelial Dystrophy versus Bullous Keratopathy: Histopathology and Clinical Results

Abstract: DMEK produces similar results for FED and BK. However, the postoperative course may differ with regard to the recurrence of secondary graft detachments that may be associated by histopathologic particularities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Oellerich et al 14 showed similar results in a multicenter study with 2485 eyes with a follow-up of 12 months. In the study by Brockmann et al 15 with 12 months follow-up, again, no significant difference could be observed at the end of the observation period.…”
Section: Discussionmentioning
confidence: 81%
“…Oellerich et al 14 showed similar results in a multicenter study with 2485 eyes with a follow-up of 12 months. In the study by Brockmann et al 15 with 12 months follow-up, again, no significant difference could be observed at the end of the observation period.…”
Section: Discussionmentioning
confidence: 81%
“…36 FECD is characterized by disparities in relation to the distribution of collagen and aberrant extracellular matrix, 37 whereas immunohistologic investigations have further demonstrated significant differences in the distribution of matrix proteins between patients with FECD and BK. 38 This could explain a different tissue remodeling taking place in the stroma-to-graft interface in populations with FECD and BK, determining a different rate of initial graft adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…In the silkworm moth, several other neuron types were described to play a role in pheromone-mediated steering, which can be added to the model for increased complexity and biological relevance. Additionally, complex motor patterns are most likely mediated by not just one cell type, but by a population code across a number of descending neurons [15]. Creating larger and more integrated models of this form is a useful tool for a more complete understanding of these complex interactions.…”
Section: Discussionmentioning
confidence: 99%
“…how it might be integrated in thoracic motor centres to influence behavioural decisions. CX output neurons project to the lateral accessory lobes (LAL; figure 1), a brain region that has been described as a pre-motor centre, because several types of descending neurons that project to thoracic motor centres have post-synaptic endings in the LALs [15]. Whereas a direct effect of neuronal activity in the CX and LALs on thoracic steering reflexes has been shown in cockroaches [16] [17] [18], the anatomical identity of the involved neurons and their place in the CX circuit is not clear.…”
Section: Introductionmentioning
confidence: 99%